KORELASI BESAR SUDUT SUBCARINAL DENGAN PEMBESARAN ATRIUM SINISTRUM PADA PASIEN STENOSIS MITRAL - , Yusni Waty Simbolon; , dr. Henry Kusumo Husodoputro, Sp.Rad(K) ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Mitral stenosis is one of cardiovascular disease related to problem in mitral valves. Thus in early stage often asymptomatic. Left atrial enlargement is the common sign of chronic mitral stenosis, which sometimes will continue as cardiac aritmias, therefore increase morbidity and mortality. Left atrium lies just inferior to the cartilage junction between left and right primary bronchiâthe carinaâand directly contacted with the inferior surface of left primary bronchus. In a normal PA projection chest X-ray, left atrial chamber is hardly visualized due to its superimposition with other cardiac chambers. Left atrial enlargement will be easily noticed when there is adjacent tissues deviation. Enlarged left atrial will push left primary bronchus in superoposteriorly direction, causes increasing of the subcarinal angle. Upright PA chest X-ray is able to predict the availability of mitral stenosis from its subcarinal angle size. The larger the left atrial the bigger the size of subcarinal angle. The aim of this study was to evaluate the correlation between the subcarinal angle size and left atrial enlargement in mitral stenosis. Radiologists in periferal clinics, that sometimes struggling with limitation of diagnostic modality such as echocardiography and human resource, can use the increasing of subcarinal angle size in upright PA chest X-ray as a predictor for mitral stenosis. This is a retrospective, analytic nor-experimental study with cross sectional design in Dr. Sardjito General Hospital, on October 2013. Subjects were mitral stenosis patients who had been diagnosed by cardiologists and also as internal control group, all compatible with the inclusion and exclusion criterias. Diameter of the left atrium had been measured by echocardiography. All subjects had upright PA chest X-ray. Subjects were selected with consecutive sampling method until minimum sample obtained. Left atrial diameter and the size of subcarinal angle were measured and statistically analized using correlation test (Pearson/Spearman). Linear regression test was used to evaluate the degree of correlation. The study was conducted with a cross sectional design. Subjects were 54 mitral stenosis patients whom had been examined with echocardiography for left atrial diameter. Left atrial measurements were conducted by cardiologist. Subjects also underwent an upright chest X-ray PA examination and those should meet the inclusion and exclusion criterias with an internal comparison group. Subjects were selected by consecutive sampling at Dr. Sardjito General Hospital, in October 2013. Baseline measurement is the size of subcarinal angle. Pearson correlation analysis test revealed that r = 0.298. It was concluded that there was a significant positive correlation despite weak correlation strength between the size of subcarinal angle on an upright chest X-ray PA and left atrial enlargement in patients with mitral stenosis.